2020
DOI: 10.3390/w12010150
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Spatial Distribution of Aerobic Anoxygenic Phototrophic Bacteria in Tama River, Japan

Abstract: Aerobic anoxygenic phototrophic bacteria (AAnPB) are widely distributed and regarded as key players driving the carbon cycle in surface water of global oceans, coastal and estuary areas and in other freshwater environments (e.g., ponds and lakes). However, the abundance and spatial distribution of AAnPB in rivers is much less well-known. Here we investigated the variation of the absolute cell abundances of the total bacteria, AAnPB and cyanobacteria, at four different sites in Tama River, Japan, and the spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…For the pufM gene, 8.17 ± 1.59 x 10 5 copies.g -1 DW were retrieved in Counozouls and 3.24 ± 0.61 x 10 5 copies.g -1 DW in Männikjärve. Again, these concentrations were comparable to AAnPBs concentrations found in soils (1-50 x 10 5 copies.g -1 ) or in aquatic environments (6 x 10 4 - 12 x 10 5 copies.mL -1 ) (Lew et al, 2016; Sato-Takabe et al, 2016, 2020; Tang et al, 2018). All together, these results showed that ddPCR is a suitable and reliable method to quantify absolute gene concentrations from complex soil matrices, like peat.…”
Section: Resultssupporting
confidence: 77%
“…For the pufM gene, 8.17 ± 1.59 x 10 5 copies.g -1 DW were retrieved in Counozouls and 3.24 ± 0.61 x 10 5 copies.g -1 DW in Männikjärve. Again, these concentrations were comparable to AAnPBs concentrations found in soils (1-50 x 10 5 copies.g -1 ) or in aquatic environments (6 x 10 4 - 12 x 10 5 copies.mL -1 ) (Lew et al, 2016; Sato-Takabe et al, 2016, 2020; Tang et al, 2018). All together, these results showed that ddPCR is a suitable and reliable method to quantify absolute gene concentrations from complex soil matrices, like peat.…”
Section: Resultssupporting
confidence: 77%
“…For the pufM gene, 8.17 ± 1.59 × 10 5 copies g −1 DW were retrieved in Counozouls and 3.24 ± 0.61 × 10 5 copies g −1 DW in Männikjärve. Again, these concentrations were comparable to AAnPBs concentrations found in soils (1–50 × 10 5 copies g −1 ) or in aquatic environments (6 × 10 4 –12 × 10 5 copies mL −1 ) (Lew et al, 2016; Sato‐Takabe et al, 2016, 2020; Tang et al, 2018). Altogether, these results showed that ddPCR is a suitable and reliable method to quantify absolute gene concentrations from complex soil matrices, like peat.…”
Section: Resultssupporting
confidence: 75%
“…Hashiba, Kameda et al (2000) expressed that the urbanization and substantial land cover phenomenon in the Tokyo area has caused widespread ecological disruptions that have affected not only plant life but also animal species and ecosystem services, such as water quality regulation, soil stability, and carbon storage capacity reduction, which could be detrimental worldwide to biodiversity conservation efforts if left unchecked and unmitigated for extended periods. Studies also have shown that the ecosystem of the Tama River Basin has considerably been impacted since 1990 (Sato-Takabe, Hirose et al, 2020). Examining the vegetation within the Tama River basin holds significant importance due to its strategic location and pressing ecological issues.…”
Section: Vegetation Dynamic Studies In River Basinmentioning
confidence: 99%
“…Examining the vegetation within the Tama River basin holds significant importance due to its strategic location and pressing ecological issues. Presently, the research in this area primarily centres on investigating temperature change, stormwater management, and ecological studies (Sato-Takabe, Hirose et al, 2020;Yamashita, Sekine et al, 1986). While research on the vegetation change and its future trend is relatively scarce, the impact of urbanization on vegetation dynamics in the Tama River basin is still rarely observed.…”
Section: Vegetation Dynamic Studies In River Basinmentioning
confidence: 99%